Kinetics and Reaction Mechanism of Biothiols Involved in SNAr Reactions: An Experimental Study - Campodónico, Paola R.; Alarcón-Espósito, Jazmín; Olivares, Belén (Frontiers in Chemistry, 2022)
Few kinetic parameters, or reaction rates, are known up to date in detail about 1-chloro and 1-fluoro-2,4-dinitrobenzene (ClDNB and FDNB, respectively) with a series of biothiols in aqueous media. These biological nucleophiles with thiol groups have been widely used as a reference in nucleophile reactivity assays due to their prevalence and cellular abundance. The main aim of this study was to elucidate the reaction mechanism based on Brönsted type-plots and reactivity patterns of the electrophile/nucleophile pairs. A complete kinetic study was performed in terms of the comparison of Brönsted-type slope parameters (nuc) for the reactions and were used for assigning the mechanism and the rate-determining step associated to the reaction route. A mass spectrometry analysis demonstrated that the nucleophilic center of the biothiols is the -SH group and there is only one kinetic product. The kinetic study suggests that the reaction mechanism might be borderline between concerted and stepwise pathways. An amine-enol equilibrium for the most reactive nucleophiles appears to be the main determining factor controlling the nucleophilic attack in the nucleophilic aromatic substitution reactions investigated, highlighting the anionic form for these nucleophiles. This amine-enol equilibrium involves hydrogen bonds which stabilize the intermediate species in the reaction pathway. Thus, intramolecular bonds are formed and enhance the nucleophilic strength through the contribution of the solvent surrounding the electrophile/nucleophile pair. Finally, we highlight the importance of the formation of electrophile/nucleophile adducts that could modify structures and/or functions of biological systems with potential toxic effects. Therefore, it is essential to know all these kinetic and reactivity patterns and their incidence on other studies.